Undernutrition and Associated Factors Among Children Aged 6–23 Months in Dessie Town, Northeastern Ethiopia, 2021: A Community Based Cross-Sectional Study - Sewenet, Tesfamaryam; W/Selassie, Mulugeta; Zenebe, Yosef; Yimam, Wondwossen; Woretaw, Lebasie (Frontiers in Pediatrics, 2022)
Abstract Globally about 159, 101, and 52 million children are stunted, underweight, and wasted, respectively. According to the 2016 Ethiopian Demographic and Health Survey, about 38% of Ethiopian children are stunted and 46%, 28.4%, and 9.8% of children in Amhara Region are stunted, underweight and wasted respectively. This study aimed to assess undernutrition and associated factors among children aged 6-23 months old at Dessie town, 2021. Method: A community-based cross-sectional study was conducted from October – November 2021 in Dessie Town. 421 Mothers/ caregivers with children aged 6-23 months old were selected by a systematic sampling method from the health extension registration book. Epi-data 3.01 was used for data entry, SPSS version 20 for statistical analysis, and WHO Anthro version 3.2.2 software for calculating the z scores. Binary logistic regression and multivariate logistic regression were used to analyze the data. AOR with 95% CI and P-values less than 0.05 were considered to see the statistical significance. Results: A total of 421 mothers or care givers paired with 6-23 months old children participated in the study. The prevalence of stunting, underweight, wasting were 36.8 % (95% CI: 32%, 41.6%), 27.6 %( 95% CI: 23.6%, 32.2%) and 11.5 %( 95% CI: 8.4%, 14.7%) respectively. Sex of the child (AOR=1.55; 95% CI: 1.02, 2.34), hand washing practice (AOR=2.32; 95% CI: 1.05, 5.11) and maternal family planning use (AOR=0.39; 95% CI: 0.19, 0.77) were significantly associated with stunting. Age of child 12-17 months (AOR=4.62; 95% CI: 2.65, 8.06) and sex of the child (AOR=1.93; 95% CI: 1.21, 3.07) were associated with underweight. Age of child 12-17 months (AOR=2.25; 95% CI: 1.06, 4.78) and action on drinking water (AOR=0.21; 95% CI: 0.07, 0.59) were associated with wasting. Conclusion and recommendation: In this study, the prevalence of undernutrition among children aged 6-23 months was higher for stunting (36.8%), underweight (27.6%) and wasting (11.5%) compared to WHO classification. Improved access to water, hygiene and sanitation, family planning services, avoiding gender discrimination during child feeding, and age-appropriate feeding practices are recommended. Moreover, implementation of public policies on food and nutrition is required for children 6-23 months of age.